Marketing capabilities in exporting companies - Vicente, Margarida (2017)
The export marketing literature has demonstrated that marketing capabilities are key drivers of export market effectiveness. However, researchers highlight the need to understand better the antecedents that may influence the development of marketing capabilities in export markets. Drawing on the resource-based view, this study investigates the way that export commitment and innovativeness contribute to the development of marketing capabilities, and the effect all these factors will have on export market effectiveness. We use a survey data of 471 exporting manufacturing companies based in Portugal to test the relationships between the constructs analysed in this study. The findings demonstrate that a high export commitment tends to cultivate a higher degree of innovativeness, which in turn allows companies to develop superior marketing capabilities. Both export commitment and two marketing capabilities, specifically product development and communication, have a direct impact on export market effectiveness. The results provide guidelines for managers and generate new directions for future research works.